Geografia escolar inclusiva: percepções, experiências e demandas de docentes, de alunos com deficiência e de licenciandos em Geografia - Brinco, Lucian Armindo da Silva (2023)
Reflecting on the inclusion of students with disabilities in Geography education in contemporary times is essential. The inclusion process is part of a recent, necessary, and emerging discussion within Brazilian education and the Geography curriculum, in particular, aiming for effective social and educational inclusion in the country. Therefore, the objective of this research was to analyze the perceptions of Geography teachers and students with disabilities in Restinga Sêca, RS, and the experiences of Geography graduate at the Federal University of Santa Maria (UFSM) regarding the developments of Inclusive School Geography in these two realities. Therefore, interviews were conducted with Geography teachers and students with disabilities from elementary and high schools in the mentioned municipality, as well as w Geography graduate at different stages of the course at the respective University. Additionally, both qualitative and, at times, even quantitative approaches were used to guide the research and analyze the results. Thus, based on the findings, it was considered that there have been advances in the inclusion process of students with disabilities, both in schools in the municipality of Restinga Sêca and in the Geography Education course at UFSM. However, that inclusion is perceived as a challenge, both in Basic Education and Higher Education. There is a context of precariousness and/or lack of infrastructure in the regular education institutions of the studied municipality that hinders effective and quality inclusion of everyone in school and in Geography. Although many respondents discuss about the importance of partnerships, public schools still cannot fully work in the perspective of Universal Design for Learning (UDL) and co-teaching, mainly due to the working conditions and the extracurricular Specialized Educational Assistance (SEA), which perpetuates the integrationist system within regular schools. In some cases, the perpetuation of exclusionary thoughts occurs because there is a justification that the lack of learning by the student with a disability is due to their biological situation. Initial and ongoing teacher training is needed to qualify individuals to better meet the different demands of the school space. However, the courses should not be seen as the only solution, as future or practicing teachers need to work on their self-training to significantly and appropriately contribute to the teaching and inclusion processes of students with disabilities, Autism Spectrum Disorder (ASD), and/or High Abilities in Geography education. Therefore, before the analysis, it can be said that truly Inclusive School Geography is not yet experienced in regular schools in the municipality of Restinga Sêca, and even with advances and curricular changes, there are obstacles that need to be overcome in the Geography Course at UFSM, so that it truly works from an inclusive perspective. The results lead to the conclusion that debates, modifications it is engagement are lacking, both in schools and universities, so that the target audience for special education to truly enjoy equitable, public, meaningful, quality, and inclusive Geography education.